EFEKTIVITAS SIDANG DI LUAR GEDUNG PENGADILAN DALAM PENYELESAIAN PERKARA ISBAT NIKAH TAHUN 2022 DI PENGADILAN AGAMA MAROS KELAS I B - Rifda Cahya Alindah Alindah; Musyfikah Ilyas; Muhammad Fajri (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem in this research is how effective the trial outside the court building held by the Maros Religious Court class I B, especially in the settlement of the marriage isbat case, then in formulating the sub-problems, namely: 1) What are the factors that hinder and support the trial outside Maros Religious Court building class I B in the settlement of the isbat marriage case in 2022? 2) What is the impact of the trial outside the Maros Religious Court building class I B in the settlement of the isbat marriage case in 2022? This research is included in qualitative field research (field research) using qualitative methods, in which this study focuses on collecting data from predetermined informants. The approach used in this thesis research is an empirical juridical and social/sociological approach because the data needed are data in the form of interviews from judges, clerks, respondents, the community and others for the author. The results of this study are that the effectiveness of the trial outside the court building in 2022 is very good and effective, because it has reached a standard level of satisfaction where the court has followed the existing policy to conduct a trial outside the court building so that the public does not have difficulty applying for itsbat married at the trial. Lack of obstacles during the trial due to complete and adequate facilities or infrastructure. As for the impact of holding a trial outside the Maros Religious Court class I B building, which is to raise legal awareness for people whose marriages are not legally valid to immediately perform isbat marriage and get a marriage certificate so that it is recognized by law and the state, more and more people are getting legal certainty in taking isbat marriage outside the courthouse and more and more areas are getting legal services easily. The implications of the research are 1. Socialization related to hearings outside the court building, especially in the settlement of isbat marriage cases to the public to better know the importance of a legal marriage. 2. For the Maros Religious Court class I B as the agency authorized to handle hearings outside the court, the court must try to maximize the trial process so that the trial runs smoothly. Keywords: Effectiveness, Isbat Marriage, Court